Elevated plasma D-dimer levels in dermatomyositis patients with cutaneous manifestations - Habe, Koji; Wada, Hideo; Higashiyama, Ayaka; Akeda, Tomoko; Tsuda, Kenshiro; Mori, Ryoko; Kakeda, Masato; Yamanaka, Keiichi; Mizutani, Hitoshi (Scientific reports, 2019)
To explore the influence of dermatomyositis (DM)-specific cutaneous manifestations (scm) on systemic coagulation and fibrinolysis, we retrospectively studied plasma D-dimer levels with/without venous thromboembolism (VTE), malignancy, infection or other connective tissue diseases (CTDs) and scm. One hundred fifty patients with DM were retrospectively investigated using medical records regarding scm, VTE, malignancy, infection, other CTDs, laboratory data and systemic corticosteroid therapy. All DM patients were categorized as follows: group 1, without scm, VTE, infection, malignancy or other accompanying CTDs; group 2, with scm only; and group 3, with VTE, infection, malignancy and other accompanying CTDs but without scm. The D-dimer plasma levels were significantly increased in group 3 compared with healthy subjects and those in groups 1 and 2 ( p < 0.001). The D-dimer plasma level in group 2 was significantly increased compared with healthy subjects and those in group 1 ( p < 0.001). Increased D-dimer plasma levels were detected in DM patients with scm without detectable VTE, malignancy, infection or accompanying CTDs. In addition to the known risk factors for increased plasma D-dimer levels in DM patients, including VTE, malignancy, infection and other accompanying autoimmune diseases, the presence of cutaneous manifestations should be considered as a new clinical risk factor.